Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor - Nurul Fatikasari; Rusdi (Akuntabel: Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine the factors that influence motor vehicle tax compliance (a case study at the West Lombok Gerung Samsat office). So that the research variables consist of 5 (five independent variables) namely tax literacy (X1), taxpayer awareness (X2), tax sanctions (X3), tax services (X4), and taxpayer sincerity (X5), and the dependent variable is compliance taxpayers (Y). The population of this study were all registered taxpayers in the Gerung Samsat area of West Lombok. The samples were taken using accidental sampling. The data were obtained by distributing 100 questionnaires to respondents in the Gerung area of West Lombok. The questionnaires were redistributed all 100. This study uses multiple linear regression analysis method.The results of this study indicate that taxpayer awareness (X2), tax sanctions (X3) and tax services (X4) do not affect taxpayer compliance.In contrast, tax literacy and taxpayer sincerity affect taxpayer compliance.The results of this study also show that the independent variable (tax literacy, taxpayer awareness, tax sanctions, tax service and taxpayer sincerity) is 64.1%. While the remaining 35.9% is influenced by other external variables that are not examined.